Investigations on microstructure and mechanical properties of HfC particle-reinforced WMo composites. (November 2021) - Liu, X.S.; Liu, M.; Zhao, X.M.; Li, R.; Sun, B.Z.; Qi, Y.; Song, J.P.
Abstract: The W-Mo-HfC composites were prepared by using the conventional powder metallurgy with the two different sintering temperature and the same forging technology. The phase component, microstructure and mechanical properties of composites were investigated, and the effects of second phase particles were focused on particularly. The two types of W-Mo-HfC composites are composed of the WMo matrix, HfC and HfO2 second phase particles. As a result, the W-Mo-HfC composite sintered at 2100 °C can yield a higher tensile strength of 993 MPa and a larger elastic modulus of 336.3 GPa. Firstly, a relatively lower sintering temperature gives rise to a smaller average grain size of the WMo matrix and the size of second phase particles, which effectively utilizes the fine grain strengthening mechanism. Secondly, HfC second phase particles at the grain boundary have the ability to capture oxygen impurity and increase the bonding strength of interface. In addition, the enhancement mechanisms of HfC particles were proposed. Highlights: Composites sintered at 2100 °C have finer matrix grains and secondary particles. The HfC particle purifies the grain boundary by oxidation reaction. Composites sintered at 2100 °C can yield a superior tensile strength.